Modulatory Effects of the Kuwanon-Rich Fraction from Mulberry Root Bark on the Renin–Angiotensin System - Ji-Hae Lee; Heon-Woong Kim; So-Ah Kim; Wan-Taek Ju; Seong-Ryul Kim; Hyun-Bok Kim; Ik-Seob Cha; Seong-Wan Kim; Jong-Woo Park; Sang-Kuk Kang (Foods, 2024)
In this study, we investigated the anti-hypertensive properties of mulberry products by modulating the renin–angiotensin system (RAS). Comparative analysis showed that the ethyl acetate fractions, particularly from the Cheongil and Daeshim cultivars, contained the highest levels of polyphenols and flavonoids, with concentrations reaching 110 mg gallic acid equivalent (GE)/g and 471 mg catechin equivalent (CE)/g of extract, respectively. The ethyl acetate fraction showed superior angiotensin-converting enzyme (ACE) inhibitory activity, mainly because of the presence of the prenylated flavonoids kuwanon G and H. UPLC/Q-TOF-MS analysis identified kuwanon G and H as the primary active components, which significantly contributed to the pharmacological efficacy of the extract. In vivo testing of mice fed a high-salt diet showed that the ethyl acetate fraction substantially reduced the heart weight and lowered the serum renin and angiotensinogen levels by 34% and 25%, respectively, highlighting its potential to modulate the RAS. These results suggested that the ethyl acetate fraction of mulberry root bark is a promising candidate for the development of natural ACE inhibitors. This finding has significant implications for the management of hypertension through RAS regulation and the promotion of cardiovascular health in the functional food industry.